Control de hábitos alimenticios a través de una aplicación telemática inteligente (2016)
Due to the increase of overweight and diseases derived from it, it is necessary that the population begins to regulate better their eating habits. Many applications can be found that help regulate people's nutrition. However, those applications are not completely useful because it does not has all the food that are commonly eat by the colombian population. That is why this project was created. In other words, through a mobile application the user would improve his food habits by recommendation done by the app. Those menus are healthy, balanced and based on their preferences and the number of calories they should consume. Also, in the app, the user can insert his daily physical activities. The base of the app is a content-based system recommendation. However, it is important to emphasize that this application does not seek to replace a nutritionist, but to complement his consultation. This means that this application does not have specific diets for diseases not so common. In fact, all the menus were recommended by a specialist.